Genome-Wide Association Study of Hepatitis in Korean Populations - Youngbok Hong; Sejong Oh (Genomics & Informatics)
Hepatitis is a common and serious disease for the Korean population. It is caused by a virus, the A and B types of which are plentiful in Koreans. In this study, we tried to find genetic factors for hepatitis through genome-wide association studies. We took 368 cases and 1,500 controls from Anseong and Ansan cohort data. About 300,000 single-nucleotide polymorphisms and 20 epidemiological variables were analyzed. We did not find any meaningful significant single nucleotide polymorphisms, but we confirmed the influence of major epidemiological variables on hepatitis.